Molecular Wires with Controllable π‐Delocalization Incorporating Redox‐Triggered π‐Conjugated Switching Units. Issue 6 (24th August 2018) - Nojo, Wataru; Tamaoki, Hitomi; Ishigaki, Yusuke; Katoono, Ryo; Fujiwara, Kenshu; Fukushima, Takanori; Suzuki, Takanori
Abstract: A perfluorobiphenyl‐2, 2′‐diyl dication and its corresponding dihydrophenanthrene‐type electron donor are interconvertible upon two‐electron transfer. Redox‐triggered C−C bond‐formation/cleavage caused a drastic change in the torsion angle of the biphenyl unit. Thus, π‐delocalization ON/OFF switching was observed as a change in the UV absorption upon electrolysis of the linearly extended analogue with two phenylethynyl groups. A further extended π‐system with a molecular length of ca. 3.5 nm, which has two switching units, was synthesized. Spectroelectrograms as well as voltammetric analyses showed that the two units act nearly simultaneously because of the very small inter‐unit electrostatic repulsion in the tetracationic state. Thus, the present pair is a promising candidate as a switching unit for "molecular wires" with controllable π‐delocalization, in which a higher ON/OFF ratio of delocalization could be realized by incorporating multiple switching units. Abstract : Due to the drastic change in the torsion angle upon 2e‐oxidation of tetraaryldihydrophenanthrene to biphenyl‐2, 2′‐bis(diarylmethylium), this redox pair can be used as a switching unit in linearly extended π‐conjugated systems, which were synthesized via SN Ar and cross‐coupling reactions. Multiple switching units act nearly simultaneously, and thus promise a higher ON/OFF ratio in molecular wires, the π‐delocalization of which can be controlled by an external stimulus.